Introduction of Institution and Program of the International Non-Government Organization on Child Protection Efforts in the Jabodetabek Area - RR Endah Sulistyaningsih; Alfrojems Alfrojems (Asian Social Work Journal, 2020)
The aim of this research is to describe the introduction of International Non-Government Organization (INGO) institutions and programs received by beneficiaries. To meet these objectives, this research method uses quantitative descriptive type. The sampling technique used is stratified proportional sampling. The number of respondents in this study amounted to 325 respondents. The results revealed that this study indicate that most people have an introduction to the program in the intermediate category.